Konsep Pluralisme dan Konflik Dalam Bingkai Kearifan Hukum dan Ekonomi Islam - Syamsuar (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2017)
The development of pluralist thinking need to be wary, because in the contemporary development has been the emergence of thinking turns the intention to destroy the Muslims through his aqidah of Muslim intellectuals themselves. This fact shows that religion acts as a development frame a theology that explores the intersection of religion in creating live together in harmony, among people of different faiths both international, regional and national scale, there are always two forms of the attitude, among others: First, mutual respect and respect that goes consciously. This means that one respects people of other faiths it is only because of political interests. Secondly, respect for the people who embrace other religions arise not only because of political interests but more than that ofan awareness that the religious affiliation of people in this world have a meeting point that is very fundamental. Islam also contains signs and limits of tolerance as His word in Surah al-An’am: 108. The fraternity as a human being and compatriots (ukhuwah Basyariah and ukhuwah wathaniyah) between a Muslim and non-Muslims at all prohibited by Muslims. The Word of God in Surat Al-Mumtahanah: 8. Religious harmony in the concept of Islam is also explained by the prophetic traditions of the Prophet Muhammad, narrated by Muslims and Bukhari. The verses and hadiths above explains that believers should not be angry when dealing with people of different religions, and must be able to resist the temptation to carry out violence, such as imposing the faith of others, social pressure of political and economic, to persuade by treasure or position, or take advantage in other artificial ways. Forced faith is not faith, they should work with the spiritual way and let God give him guidance. Hopefully, this article may provide insight for us to be aware of the movements of thought plural.